2015
DOI: 10.1542/peds.2014-3434
|View full text |Cite
|
Sign up to set email alerts
|

Academic Effects of Concussion in Children and Adolescents

Abstract: The aim of this work is to study the nature and extent of the adverse academic effects faced by students recovering from concussion.METHOD: A sample of 349 students ages 5 to 18 who sustained a concussion and their parents reported academic concerns and problems (eg, symptoms interfering, diminished academic skills) on a structured school questionnaire within 4 weeks of injury. Postconcussion symptoms were measured as a marker of injury severity. Results were examined based on recovery status (recovered or act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
158
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(177 citation statements)
references
References 10 publications
6
158
1
2
Order By: Relevance
“…The injury incidence we showed for AASE players is concerning given the negative effect sports injuries can have on school attendance and sports participation. 18 Ransom et al 19 found negative academic effects in those recovering from concussion, which may further affect AASE players given the high concussion rate during AASE matches.…”
Section: Injury Incidencementioning
confidence: 99%
“…The injury incidence we showed for AASE players is concerning given the negative effect sports injuries can have on school attendance and sports participation. 18 Ransom et al 19 found negative academic effects in those recovering from concussion, which may further affect AASE players given the high concussion rate during AASE matches.…”
Section: Injury Incidencementioning
confidence: 99%
“…21 Regardless, the academic demands of secondary school education may warrant the facilitation of timely, informal academic adjustments to prevent falling behind and to reduce school-related anxiety. 4 Athletic trainers can help bridge the gap between medical recommendations and school implementation by becoming more familiar with return-to-learn resources and school and district policies and by communicating more frequently with school professionals.…”
Section: Cognitive Rest and Academic Supportmentioning
confidence: 99%
“…3 Yet compliance with cognitive rest may pose challenges for adolescents during the academic year. 4 Patients have often reported returning to school before concussion symptoms have subsided, 5 which may prolong recovery and affect academic performance. Previous researchers 6,7 have observed an increase in symptoms and a decrease in cognitive performance with bouts of cognitive activity after concussion.…”
mentioning
confidence: 99%
“…In addition, 63% reported a decline in grades. This is not surprising given the findings by Ranson, et al that the more symptoms a post-concussed patient had while in school the more poorly they performed academically [15].…”
mentioning
confidence: 83%